Unpacking Consumer Behavioral Intentions in Sustainable Cosmetics: The Role of Green Brand Love and Trust - Nadiyah Asmaranti Anita Putri; Ananda Sabil Hussein; Taufiq Ismail (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The cosmetics industry in Indonesia contributes significantly to environmental degradation through non-degradable packaging and chemical-laden products, prompting a shift toward eco-friendly alternatives. Consumer demand for sustainable cosmetics is growing, driven by environmental awareness, yet the factors influencing their purchasing behavior remain underexplored. This study aims to examine how green motivation influences behavioral intentions toward eco-friendly cosmetic products, with green brand love and green trust as mediators, focusing on the Indonesian market. A quantitative approach was employed, collecting data through an online survey from 262 Indonesian consumers who had purchased green cosmetics. The data were analyzed using Structural Equation Modeling-Partial Least Squares to test the relationships between variables. The findings reveal that green motivation significantly influences behavioral intentions, with green brand love and green trust partially mediating this relationship. Consumers with strong environmental motivation exhibit greater emotional attachment and trust in eco-friendly brands, enhancing their likelihood to purchase and recommend these products. This study concludes that fostering genuine sustainability practices can strengthen consumer loyalty in Indonesia’s green cosmetics market, offering insights for brands to align with environmental values and meet growing consumer expectations.